Ответ(ы) на вопрос:
Вот-это же легко...
2 1/7*3 8/15+1 7/15*2 2/7-7 2/7*5=
2 2/7*3 8/15=848/105=8 8/105
1 7/15*2 2/7=352/105=3 37/105
7 2/7*5=255/7=36 3/7
8 8/105+3 37/105=11 3/7
11 3/7-36 3/7=-25
= 2 2/7 * (3 8/15 + 1 7/15) - 7 2/7 * 5 = 2 2/7 * 5 - 7 2/7 * 5 = 5 * (2 2/7 - 7 2/7) = 5 * (-5) = - 25
Пояснения:
1) Выносим общий множитель 2 2/7 за скобки:
= 2 2/7 * (3 8/15 + 1 7/15) - 7 2/7 * 5 = 2 2/7 * 5 - 7 2/7 * 5
2) Выносим общий множитель 5 за скобки:
5 * (2 2/7 - 7 2/7) = 5 * (-5) = - 25
Не нашли ответ?
Похожие вопросы